Opportunities and Barriers for Valorizing Waste Incineration Bottom Ash: Iberian Countries as a Case Study - Bandarra, Beatriz S. (2021)
Incineration bottom ashes (IBA) are the main waste from municipal solid waste (MSW) incineration. In the Iberian countries (Portugal and Spain), MSW incineration with energy recovery (WtE) plays an important role in MSW management. IBA is highly produced and managed differently both between and within countries. This paper aims to provide a comprehensive overview of the management model of IBA using the Iberian Peninsula as a case study, addressing its properties, current management, incentives and difficulties in valorizing, and prospects. For this purpose, incineration plants of both countries were approached, and a broad literature review was conducted to gather information. About 10% and 41% of IBA have been landfilled in Portugal and Spain, respectively. Metals (mostly ferrous) from Portuguese (6% of IBA) and Spanish (9% of IBA) WtE plants are recycled. In Portugal, the remaining IBA (84%) has been temporarily stored (11%), applied to landfills as a substitute for soil in intermediate and final covers, construction of paths, accesses, and platforms (41%), or used in civil engineering work and road construction (48%). In Spain, the remaining IBA (50%) has been reused mainly as a secondary raw material in the construction and civil engineering fields (77%), while the rest has been temporarily stored (11%), applied in the conditioning of landfills (4%), alsoa secondary aggregate replacing natural materials. Both countries regulate IBA reuse outside landfills but consider different requirements and criteria. Nevertheless, there are both drivers and barriers to valorization. In the future, different IBA applications will likely continue to be developed, with the concern of protecting the environment. Growing confidence in IBA reuse following the publication of proper studies is expected. Globally, uniform legal frameworks among EU members with the same standards would likely lead to better IBA valorization.